Delayed mid-basilar artery stenosis following paediatric acute mechanical thrombectomy: a rare complication from a rare case. Issue 8 (2nd August 2019) - Mukherjee, Soumya; McCullagh, Helen; Goddard, Tony; Patankar, Tufail
Abstract : There is limited literature on the use of mechanical thrombectomy with stent-retrievers in paediatric stroke, especially in the posterior circulation. We report a paediatric case of acute basilar artery occlusion successfully treated by mechanical thrombectomy using stent-retriever but complicated by delayed basilar artery stenosis. This case emphasises prudent selection of thrombectomy device and meticulous long-term follow-up when employed in paediatric stroke.